Optimalisasi Perlombaan Perayaan 1 Muharram Untuk Penguatan Nilai Spiritual Anak Di Masjid Al-Iqra Desa Meok - Putra, Deko Rio; Witama, Muhammad Faizal; Melyasari, Eliza; Wati, Devi Setia; Sari, Dewa Ayu Purnama; Sari, Prima Dwi Putri; Yati, Harlinda; Rahmadaniati, Rossa; Erliyanti, Junita; Khoirun, Alfa Ridzi Misbaqul; Setiawan, Dimas; Kurniawan, Ego (Pakis Journal Institute, 2024)
This study examines the role of Islamic competitions in the 1 Muharram celebration held at Al-Iqra Mosque in Meok Village, as an effort to strengthen the spiritual values of the local children. This program is part of the Community Service Program (KKN) Group 8 from UIN Fatmawati Sukarno Bengkulu’s Outer Islands, focusing on enhancing children’s awareness and understanding of Islamic teachings through various competitions such as short surah memorization, adhan, Islamic calligraphy coloring, and Muslim attire. This research employs a descriptive qualitative method with a case study approach, and data were collected through observation, interviews, and literature review. The findings indicate that the activities successfully fostered Islamic enthusiasm and increased religious understanding among the children. Additionally, the competitions created an atmosphere of togetherness and creativity, strengthening the bonds between children, families, and the community in celebrating this important religious event.